The Effect of Promotion, Brand Image, and Price Perception on Purchasing Decisions at Fashion Item Oseng Deles Banyuwangi - Nova Auliatul Faizah; Nilawati, Wardha; Kadek Yuliandari, Ni (Journal of Accounting and Finance Management, 2024)
Oseng Deles is a typical Banyuwangi souvenir centre shop that provides fashion products, such as t-shirts. This study aims to analyse the effect of promotion, brand image, and price perception on purchasing decisions for fashion item products at Oseng Deles Banyuwangi simultaneously and partially. The population of this study were customers of fashion item products at Oseng Deles Banyuwangi, with 100 respondents as samples selected using simple random sampling technique. Data collection methods include observation, questionnaires, interviews, and documentation. This research is a type of descriptive quantitative research that uses multiple linear regression analysis, the coefficient of determination, partial test (t test), and simultaneous test (F test). The results showed that promotion, brand image, and price perceptions simultaneously and partially have a significant effect on customer satisfaction.